Pengaruh Kombinasi Jus Belimbing Wuluh dan Mentimun terhadap Penurunan Tekanan Darah pada Wanita Dewasa Penderita Hipertensi Rawat Jalan di Kabupaten Bekasi Tahun 2022 - Serlita Sari Rahayu; Yenny Aulya; Retno Widiowati (Jurnal Akademika Baiturrahim Jambi, 2022)
Hypertension is a manifestation of hemodynamic balance disorders of the cardiovascular system, where the pathophysiology is multi-factorial, so it cannot be explained by only one single mechanism. Some plants in Indonesia that need to be considered as blood pressure lowering are wuluh starfruit (Avverhoa bilimbi L) and cucumber (Cucumis sativus L). This study aimed to determine the effect of giving a combination of star fruit juice and cucumber to decrease blood pressure in adult women with hypertension outpatients in Bekasi Regency in the experimental group and the control group. This quasi-experimental study used a pre and post-test with control group design. The sample in this study was 36 patients with hypertension class 1 consisting of 18 patients in the experimental group and 18 patients in the control group. The sampling technique used wasv purposive sampling technique. The research instrument uses standard operating procedures. Data analysis had been done Paired t-test if the data was normally distributed, and if the data is not normally distributed using the Wilcoxon and Man-Whitney test which is a nonparametric test. Wilcoxon test in the systolic and diastolic experimental groups obtained P-Value 0.000. The control group had systolic P-Value 0.004 and diastolic P-Value 0.034. In the Mann-Whitney Systolic and diastolic test in the experimental group and the control group, 2-tailed Asymp.Sig was 0.000. There was a significant difference in the effect of reducing blood pressure in adult women between the control group and the experimental group given a combination of star fruit and cucumber juice. It is hoped that the combination of starfruit juice and cucumber to reduce blood pressure of hypertension sufferers can be applied in health services